(p)ppGpp: Magic Modulators of Bacterial Physiology and Metabolism - Steinchen, Wieland; Zegarra, Victor; Bange, Gert (Frontiers in Microbiology, 2020)
When bacteria experience growth-limiting environmental conditions, the synthesis of the hyperphosphorylated guanosine derivatives (p)ppGpp is induced by enzymes of the RelA/SpoT homology (RSH)-type protein family. High levels of (p)ppGpp induce a process called ‘stringent response’, a major cellular reprogramming during which rRNA and tRNA synthesis is downregulated, stress-related genes upregulated, mRNA stability and translation altered, and allocation of scarce resources optimized. The (p)ppGpp-mediated stringent response is thus often regarded as an all-or-nothing paradigm induced by stress. Over the past decades, several binding partners of (p)ppGpp have been uncovered displaying dissociation constants from below one micromolar to more than one millimolar and thus coincide with the accepted intracellular concentrations of (p)ppGpp under non-stringent (basal levels) and stringent conditions. This suggests that the ability of (p)ppGpp to modulate target proteins or processes would be better characterized as an unceasing continuum over a concentration range instead of being an abrupt switch of biochemical processes under specific conditions. We analyzed the reported binding affinities of (p)ppGpp targets and depicted a scheme for prioritization of modulation by (p)ppGpp. In this ranking, many enzymes of e.g., nucleotide metabolism are among the first targets to be affected by rising (p)ppGpp while more fundamental processes such as DNA replication are among the last. This preference should be part of (p)ppGpp’s ‘magic’ in the adaptation of microorganisms while still maintaining their potential for outgrowth once a stressful condition is overcome.